2017
DOI: 10.1016/j.aller.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of Streptococcus pneumoniae serum antibodies in patients with primary immunodeficiency on regular intravenous immunoglobulin treatment

Abstract: Pneumococcal antibodies are present in a high range of concentrations in sera from PID patients and also in IVIG preparations. Even maintaining a recommended IgG trough level, these patients can be susceptible to these bacteria and that may contribute to recurrent respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This suggests that the initial concentration of specific antibodies in an IgG preparation determines the antibody levels achieved in vivo. Interestingly, circulating antibody levels were very similar to antibody concentrations achieved with weekly subcutaneous infusions …”
Section: Pneumococcal Immunity In Human Gamma Globulinsupporting
confidence: 59%
See 1 more Smart Citation
“…This suggests that the initial concentration of specific antibodies in an IgG preparation determines the antibody levels achieved in vivo. Interestingly, circulating antibody levels were very similar to antibody concentrations achieved with weekly subcutaneous infusions …”
Section: Pneumococcal Immunity In Human Gamma Globulinsupporting
confidence: 59%
“…Interestingly, circulating antibody levels were very similar to antibody concentrations achieved with weekly subcutaneous infusions. 39,40 Tuerlinckx et al 41 observed that distribution curves differed between serotypes and showed wide dispersion among patients. In 89% to 100% of patients, antibodies against most serotypes reached trough levels of 0.2 μg/mL, a threshold they considered protective against invasive pneumococcal infection.…”
Section: Pneumococcal Immunity In Human Gamma Globulinmentioning
confidence: 99%
“…B cell deficiency has often been associated with the impairment of immunity against infection. Individuals with X-linked agammaglobulinemia (XLA) have a mutation in the gene that is responsible for Bruton tyrosine kinase (BTK), which involves a failure in antibody production and a high susceptibility to bacterial infections (Simao-Gurge et al, 2017). There is a murine model that exhibits the same impairment and leads to a similar state of susceptibility to that in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Simão‐Gurge et al measured total IgG levels as well as pneumococcal IgG for six serotypes via WHO ELISA in trough serum samples from 21 pediatric and adult patients receiving IVIG. These levels were compared to total IgG and pneumococcal IgG levels from the IVIG preparations that were administered to the participants.…”
Section: Pneumococcal Antibodies In Immunoglobulin Productsmentioning
confidence: 99%